China Revamping Decades-Old Fisheries Law to Combat Illegal, Unreported, and Unregulated Fishing: Stimulating the Intersection of Law, Technology, and Markets - He, Juan; Zhang, Xiong (Frontiers in Ecology and Evolution, 2022)
As the world’s leading fish producer, exporter and consuming State, China must act decisively to eradicate national and international commerce in wild-capture species derived from illegal, unreported and unregulated fishing. In 2019 China launched an extensive overhaul of the 1986 Fisheries Law with a new draft debated at the 2020 National People’s Congress. In this policy paper, we argue that China should not miss the opportunity but proactively align with the global paradigm shift towards responsible and sustainable fisheries management. To amend the patchy legal framework and implement the rule of law ahead, we suggest technology-enabled traceability and market-responsive solutions to mitigate illicit capturing, processing and transaction events infiltrating from bait to plate throughout a Chinese supply chain.